Analysis for sparsely sampled phased array antenna for advanced Doppler radar - Mohd. Isa, Farah Nadia; Brennan, Paul V. (2014)
This paper documents the study of a sparsely sampled phased array antenna used for an avalanche radar in VDLS. The fully populated array of 144 elements (16 × 9) is analysed and some of the prominent result are tabulated in this paper findings. The thinning method is based on the previous knowledge of the iterative method compiled by the author. It is shown that with the right thinning of the antenna elements, the beampattern of the phased array antenna could be controlled to give the desired pattern to the designer.